The Arabs at War in Afghanistan - Hamid, Mustafa and Farrall, Leah (London Hurst & Company, 2015)
A former senior mujahidin figure and an ex-counter-terrorism analyst cooperating to write a book on the history and legacy of Arab-Afghan fighters in Afghanistan is a remarkable and improbable undertaking. Yet this is what Mustafa Hamid, aka Abu Walid al-Masri, and Leah Farrall have achieved with the publication of their ground-breaking work. The result of thousands of hours of discussions over several years
Include Note and Index
Keywords: Afghanistan -- Soviet Occupation of Afghanistan (1979-1989) -- Taliban -- Qaida (Organization)